Antioxidant Activity of Fullerenols. Bioluminescent Monitoring in vitro. (2017) - Sachkova, A.S.; Kovel, E.S.; Vorobeva, A.A.; Kudryasheva, N.S.
Abstract: Bioluminescence of isolated enzymes is a perspective phenomenon for biosensors development due to simplicity of registration of a physiological parameter - light intensity. Enzyme-based bioluminescent assay is widely used to evaluate a decrease in biochemical toxicities. Also the enzyme-based assay is used for the direct biochemical monitoring of oxidative toxicity. This work considers antioxidant properties of fullerenols, water-soluble polyhydroxylated derivatives of fullerenes and perspective pharmaceutical agents, in solutions of model inorganic and organic toxicants of oxidative type – K3 [Fe(CN)6 ] and 1, 4-benzoquinone. Two fullerenol preparations were used: C60 O2-4 (OH)20-24 and mixture of two types of fullerenols C60 O2-4 (OH)20-24 +C70 O2-4 (OH)20-24 . The enzyme-based assays showed the peculiarities of the detoxification processes: ultralow concentrations of fullerenols were active ( ca 10 -17 -10 -5 g/L); no monotonic dependence of detoxification efficiency on fullerenol concentrations was observed, and detoxification of organic oxidizer solutions was more effective than that of the inorganic oxidizer. The antioxidant effects of highly diluted fullerenol solutions were attributed to hormesis phenomenon; the detoxification was concerned with stimulation of adaptive cellular response under low-dose exposures.